2019
DOI: 10.1111/jfbc.12997
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and SREBP1 functional analysis of mammary epithelial cell inbuffalo

Abstract: Compared to cow milk, buffalo milk contains more protein, fat, and vitamin. Buffalo milk is an ideal food in human life. Sterol regulatory element‐binding protein 1 (SREBP1), an important transcription factor, regulates the expression and activity of enzyme and protein involved in milk fat synthesis to influence on the synthesis and secretion of triglyceride in mammary epithelial cells. In the present study, we successfully isolated buffalo mammary epithelial cell by using enzymatic digestion, and then describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is generally accepted that PPAR γ is a critical factor for lipogenesis and has relationships with other lipogenic genes (Farmer, 2006; Rosen and MacDougald, 2006; Siersbaek et al ., 2012). In buffalo, SREBP1 gene may act on ERK1 / ERK2 signaling pathway to regulate the expression of PPARy gene (Xu et al ., 2019 a , 2019 b ) and, as a transcription regulator, PPAR γ is able to enhance the expression of many genes related to lipogenesis including FASN (Lefterova et al ., 2008; Zhang et al ., 2016). Moreover, many other studies have indicated that these genes (PPAR γ, FASN , SREBP1 ) are associated with milk fat synthesis in mammary epithelial cells (Yang et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that PPAR γ is a critical factor for lipogenesis and has relationships with other lipogenic genes (Farmer, 2006; Rosen and MacDougald, 2006; Siersbaek et al ., 2012). In buffalo, SREBP1 gene may act on ERK1 / ERK2 signaling pathway to regulate the expression of PPARy gene (Xu et al ., 2019 a , 2019 b ) and, as a transcription regulator, PPAR γ is able to enhance the expression of many genes related to lipogenesis including FASN (Lefterova et al ., 2008; Zhang et al ., 2016). Moreover, many other studies have indicated that these genes (PPAR γ, FASN , SREBP1 ) are associated with milk fat synthesis in mammary epithelial cells (Yang et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that SIRT2 is involved in lipogenesis (Perrini et al ., 2020; Xu et al ., 2019 a , 2019 b ; Lantier et al ., 2018) and the co-transfection experiment showed that by targeting SIRT2 , miR-212 upregulates the mRNA expression of FASN and SREBP1 but not PPAR γ. These are the first data to confirm that SIRT2 can directly regulate FASN and SREBP1 negatively, whilst the result of PPAR γ is at odds with a recent report (Xu et al ., 2019 a , 2019 b ) that in bovine ovarian granular cells, SIRT2 knockdown or treatment with inhibitors produced negative effects on PPAR γ. It was supposed that the mechanism might be SIRT2 mediating the transcription factors FOXO1 .…”
Section: Discussionmentioning
confidence: 99%
“…SREBP1 or also known as sterol regulatory element binding transcription factor 1 (SREBF1) is also essential in the fat metabolism of ruminants because it also influences the fat characteristics of both meat and dairy products. This has been demonstrated in cattle (Harvatine & Bauman 2006;Proskura et al 2017;Gamarra et al 2021;Kawaguchi et al 2021), buffalo (Deng et al 2017;Xu et al 2019), goat (Xu et al 2016), and sheep (Tsiplakou et al 2015;Liang et al 2020;Carcangiu et al 2021). In bovine, the SREBP1 gene is located on chromosome 19 with 21 exons and encodes 1183 amino acids (Hoashi et al 2007).…”
Section: Introductionmentioning
confidence: 92%